Echocardiographic Study Among Traffic Police Personnel in Central Nepal - Laudari, Shankar; Dallakoti, Samanata; Khanal, Sulav (Journal of National Heart and Lung Society Nepal, 2022)
Background: Echocardiographic studies among traffic police personnel are lacking in the world including in Nepal. So, this study is planned to detect any structural cardiac abnormalities in this specific group population. Methods: This is a cross-sectional descriptive study conducted among fifty traffic police personnel working in the Chitwan district of Nepal. All underwent two-dimensional transthoracic echocardiography in Chitwan Mutu Aspatal. Results: The age ranged from 21 to 55 years, with a mean age of 35 years. Males were predominant (46/50) and 14(28%) were diagnosed as hypertensives. Mild MR was detected on 11(22%) participants. Conclusion: This is the first reported observational study so far among the traffic police personnel in Nepal. There is a high incidence of systemic hypertension among these populations though no major cardiac structural abnormalities were detected.